1995
DOI: 10.1097/00003246-199508000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythromycin on gastric motility in mechanically ventilated critically ill patients

Abstract: In mechanically ventilated patients, intravenous erythromycin (200 mg over 30 mins) increases indices of antral motility and accelerates gastric emptying as assessed by the kinetics of acetaminophen absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
68
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(71 citation statements)
references
References 21 publications
1
68
0
2
Order By: Relevance
“…53,54 Studies comparing individual agents with placebo have demonstrated prokinetic agents to be effective for promoting gastric emptying in critically ill patients. [22][23][24][25] In a randomized, controlled study of 21 critically ill patients, Spapen et al 22 showed that cisapride promotes gastric emptying as assessed by the volume of gastric residuals and bedside scintigraphy compared with placebo. During the 7-day study period, the mean gastric residual volume was significantly higher and gastric emptying significantly slower in the placebo group than in the cisapride group (p < .005).…”
Section: !mentioning
confidence: 99%
See 4 more Smart Citations
“…53,54 Studies comparing individual agents with placebo have demonstrated prokinetic agents to be effective for promoting gastric emptying in critically ill patients. [22][23][24][25] In a randomized, controlled study of 21 critically ill patients, Spapen et al 22 showed that cisapride promotes gastric emptying as assessed by the volume of gastric residuals and bedside scintigraphy compared with placebo. During the 7-day study period, the mean gastric residual volume was significantly higher and gastric emptying significantly slower in the placebo group than in the cisapride group (p < .005).…”
Section: !mentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled, crossover study of ten critically ill patients, Dive et al 25 demonstrated the erythromycin enhances antral motility and accelerates gastric emptying compared with placebo. The mean number and amplitude of contractions and motility index were increased significantly during the first hour after erythromycin infusion (p < .005).…”
Section: !mentioning
confidence: 99%
See 3 more Smart Citations